Protective effect of remimazolam on intestinal barrier function in septic mice - WANG Weifei; DENG Haoyue; DU Yunxia (陆军军医大学学报)
Objective‍　‍To investigate the protective effects of remimazolam (Remi), a novel benzodiazepine sedative, on intestinal barrier function in septic mice. Methods A mouse model of sepsis was established using cecal ligation and puncture (CLP). A total of 96 SPF-grade adult male C57BL/6 mice were randomized into sham operation (Sham), sepsis (Sepsis), and sepsis with Remi intervention (Sepsis+Remi) groups. Survival rate and survival time were recorded within 72 h after modeling. Intestinal pathological alterations, barrier functional indicators, ZO-1 expression, and macrophage polarization status were observed and detected to evaluate the effects of Remi. Lipopolysaccharide (LPS) was used to treat RAW264.7 cells for 24 h to simulate in vitro sepsis model. The cells were divided into control (Control), LPS, and LPS+Remi groups. Immunofluorescence staining was performed to assess macrophage phenotype, mitochondrial morphology, and mitochondrial reactive oxygen species (MtROS), and Western blotting was applied to detect the protein expression of iNOS and CD206. Results Compared with the sepsis group, Remi intervention significantly improved the survival rate of septic mice from 12.50% to 68.75% and markedly prolonged survival duration (P<0.05). Histopathological analysis demonstrated partial restoration of intestinal villus architecture, accompanied with attenuated interstitial edema and reduced inflammatory cell infiltration after Remi intervention. Furthermore, the intervention group demonstrated significant improvement in functional indicators. Both in vivo and in vitro experiments demonstrated elevated iNOS and decreased CD206 expression in the septic mice and LPS-stimulated macrophages（P<0.05）, which were partially reversed after Remi intervention. Furthermore, LPS-stimulated macrophages exhibited fragmented mitochondria and elevated MtROS level, whereas Remi intervention ameliorated these conditions（P<0.05）. Conclusion‍　‍Remi protects intestinal barrier function in septic mice by mitigating mitochondrial dynamics imbalance-induced oxidative damage and ameliorating inflammatory macrophage activation.